Implementation of Efficient Teaching Scheme of Human Anatomy and Physiology Based on Multimedia Information Processing Technologies. (28th June 2022) - Ma, Yue; Zhi, Zhuangzhi
Abstract : An application scheme based on the teaching of human anatomy and physiology, namely, PBL, is proposed. In particular, 95 medical students were randomly divided into two groups: classes 2 and 3 were the experimental classes (48 students), and then, the teaching practice was carried out according to the machine learning route; year 1 and class 4 were the control classes (47 students), and the traditional teaching method was used. The teaching effectiveness was evaluated by performance analysis, the mean score of the overall evaluation of the experimental class was (93.23 ± 2.01), the mean score of the control group was (91.51 ± 2.89), and the difference was statistically significant (p < 0.01 ). The survey showed that more than 93% of the students in the experimental class thought that the deep learning model helped stimulate their interest in learning, enhance their sense of teamwork, and improve their overall ability.